The causal analysis of the development of the unemployment effect on life satisfaction - Nils Lerch (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The long-term negative effects of unemployment, especially on subjective well-being, have been indicated by many studies. Therefore, unemployment and its effects on the individual life course must remain an important challenge for social policy. Many studies have focused on the cognitive component of subjective well-being, i.e., life satisfaction, and have analysed in particular its development during the unemployment period. The trajectory is usually characterized by the effects of anticipation, reaction and adaption. Studies have shown different findings regarding the shape of the effect development. The present study discusses the effect development in greater detail and analyses whether the development of the effect is different depending on unemployment experience using longitudinal data from the German Socio-Economic Panel (SOEP) and applying fixed effects regressions. The findings of this study support a non-linear effect development, which begins with the anticipation of unemployment. The trend can be described by a linear function and polynomials up to the fifth degree. The introduction of a model according to modern causal analysis and the interpretation of the dynamic development of the counterfactual outcomes are the secondary focuses of the study. A detailed discussion of causal assumptions and necessary control variables is needed to reveal the effect of unemployment on life satisfaction. The SOEP provides information about employment status on a monthly basis. This study shows possibilities for using this information for the construction of control groups and treatment groups and analyses with ideal episode patterns.
Keywords: 330; unemployment; SOEP; life satisfaction; causal analysis; FE-estimations; cognitive well-being